Base Editing Mediated Generation of Point Mutations Into Human Pluripotent Stem Cells for Modeling Disease - Qi, Tao; Wu, Fujian; Xie, Yuquan; Gao, Siqi; Li, Miaomiao; Pu, Jun; Li, Dali; Lan, Feng; Wang, Yongming (Frontiers in Cell and Developmental Biology, 2020)
Human pluripotent stem cells (hPSCs) are a powerful platform for disease modeling and drug discovery. However, the introduction of known pathogenic mutations into hPSCs is a time-consuming and labor-intensive process. Base editing is a newly developed technology that enables facile introduction of point mutations into specific loci within the genome of living cells. Here, we design an all-in-one episomal vector that expresses an sgRNA with an adenine base editor (ABE) or a cytosine base editor (CBE). Both ABE and CBE can efficiently introduce mutations into cells, A-to-G and C-to-T, respectively. We introduce disease-specific mutations of long QT syndrome into hPSCs to model LQT1, LQT2 and LQT3. Electrophysiological analysis of hPSC-derived cardiomyocytes (hPSC-CMs) using multi-electrode arrays (MEAs) reveals that edited hPSC-CMs display significant increases in duration of the action potential. Finally, we introduce the novel Brugada syndrome-associated mutation into hPSCs, demonstrating that this mutation can cause abnormal electrophysiology. Our study demonstrates that episomal encoded base editors (epi-BEs) can efficiently generate mutation-specific disease hPSCs models.